Re-emphasizing the dimensions and impacts of complementary IT resources through governance - Ajayi, Binyamin; Ahlan, Abdul Rahman; Olanrewaju, Rashidah Funke (IEEE, 2016)
Complementary resources are organisations assets and capabilities employed in achieving value through proper information technology governance (ITG). Resources when corporately governed are bound to place organisations in positions to offer excellent services and this result into happy and loyal customers. Organisations in advanced settings are capable of such proper leverage on the value of IT than their counterparts in other worlds. The theoretical use of resource-based view and absorptive capacity construct in this paper afford richness in viewing IT resources as comprising assets and capabilities of employees in organisations. This article is an effort which by relying on a previous empirical study in the governance of IT opines that: measuring performance in financial perspectives alone is no more fashionable. There is a need to complement such efforts with operational measures like IT assets, taking into consideration the capabilities of employees in achieving performance. By proposing a framework, this article suggests that organisations have to look beyond IT asset, complementing it with the abilities of their employees to herald IT-enabled business processes. Such processes, it is assumed, will have potentials to optimise resources committed to creating lean enterprises. It is achievable by eliminating bottlenecks through re-engineered processes whereby customers serve themselves and are made to respect processes. Attention should be given to the capabilities of employees to utilise IT assets creatively.